STRATEGI PEMIMPIN DALAM MENINGKATKAN DAYA SAING SISWA LULUSAN DI ERA DIGITALISASI - Nurjanah, Siti; Bedi, Fisman; Fitri, Tin Amalia (re-JIEM (Research Journal of Islamic Education Management), 2024)
Innovative and technology-adaptive school leaders can produce curricula that prepare students to compete effectively in the digital age. This research examines the strategies of effective leaders in creating and implementing policies that drive graduate quality improvement. This research uses a qualitative approach with a type of library research that allows researchers to conduct a comprehensive investigation of various documents and relevant literature sources. The results show that modern school leaders can improve the quality of education and prepare students for the future through three main strategies: (1) organizing comprehensive digital skills training to develop students' technological competence, (2) integrating digital technology into the curriculum to ensure the relevance of learning, and (3) establishing strategic partnerships with industry to provide practical experience through internship programs and real job opportunities. These results show that leadership innovation in education is key to dealing with the rapid and complex development of digital technology, ensuring the education system remains relevant and able to prepare learners with the skills needed in the modern era.